Entrepreneurial self-efficacy and intentions: Outcome expectations as mediator and subjective norms as moderator. Issue 3 (22nd November 2019) - Santos, Susana C.; Liguori, Eric W.
Abstract : Purpose: Building on social career cognitive theory, the purpose of this paper is to investigate outcome expectations as a mediator and subjective norms as a moderator in the relationship between entrepreneurial self-efficacy and intentions. Design/methodology/approach: Using a sample of 1, 026 students from US public and private universities retrieved from the Entrepreneurship Education Project, this study tests a first-stage moderated mediation model in a two-step process. Findings: Results show that entrepreneurial self-efficacy is positively related to entrepreneurial intentions through the partial mediating effect of entrepreneurial outcome expectations, and that this relationship is consistently significant and positive for individuals with lower, average and higher subjective norms towards entrepreneurship. Research limitations/implications: These findings contribute to the literature on entrepreneurial intentions by providing a comprehensive overlook on the mechanisms and boundary conditions relevant for intentions. Practical implications: These results reinforce the need for educators and policy makers to ensure programs manage outcome expectations and recognize the role of peer, parent and mentor role models on the construction of these expectations and, consequently, on entrepreneurial intentions. Originality/value: Exploring the combined effect of entrepreneurial outcome expectations as a mechanism and subjective norms as boundary conditions on the relationship between entrepreneurial self-efficacy and entrepreneurial intentions is an unexplored issue to date, and helps to understand how and why entrepreneurial intentions emerge.